2014
DOI: 10.1159/000363106
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Dose-Dependent Pubertal Growth: A Randomized Trial in Short Children with Low Growth Hormone Secretion

Abstract: Background/Aims: Growth hormone (GH) treatment regimens do not account for the pubertal increase in endogenous GH secretion. This study assessed whether increasing the GH dose and/or frequency of administration improves pubertal height gain and adult height (AH) in children with low GH secretion during stimulation tests, i.e. idiopathic isolated GH deficiency. Methods: A multicenter, randomized, clinical trial (No. 88-177) followed 111 children (96 boys) at study start from onset of puberty to AH who had recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…In our unselected cohort of patients, there are numerous diagnoses included, and these may affect the response to treatment with rhGH. Formal dose response studies have clearly described a relationship between gain in height and growth hormone dose [27, 28], and high and low dose IGF-I generation tests also relate GH dose to increment in IGF-I [29]. Greater weight and higher growth hormone dose have been identified as predictors of first year growth response in previous cohorts of patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…In our unselected cohort of patients, there are numerous diagnoses included, and these may affect the response to treatment with rhGH. Formal dose response studies have clearly described a relationship between gain in height and growth hormone dose [27, 28], and high and low dose IGF-I generation tests also relate GH dose to increment in IGF-I [29]. Greater weight and higher growth hormone dose have been identified as predictors of first year growth response in previous cohorts of patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…The end of pubertal growth has typically not been specifically identified, and measurements have instead been based on when adult height was attained. Therefore, the total pubertal height gain has been defined as the amount of growth observed from the onset of pubertal growth until adult height, with the duration of pubertal growth defined as the time period from the onset of puberty to the attainment of adult height [2, 12, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…In children with low GH secretion diagnosed with idiopathic isolated GHD (IIGHD), we have also reported that GH dosing, mimicking the physiological pubertal increase in GH secretion, has a dose-dependent effect on the gain in height SDS until AH. In this randomized GH-treatment trial, pubertal height gain SDS and AH SDS were greater in children randomized to a high GH dose (67 μg/kg/d) than a standard dose (33 μg/kg/d) [ 18 , 19 ]. The hypothesis of the present analysis of prospectively collected data in the aforementioned clinical trial was that the IGFs would follow the normal pubertal change in GH-deficient children receiving a higher, more physiological, GH dose during puberty.…”
Section: Introductionmentioning
confidence: 99%